2018
DOI: 10.1016/j.plaphy.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Active proton efflux, nutrient retention and boron-bridging of pectin are related to greater tolerance of proton toxicity in the roots of two Erica species

Abstract: Background and aimsTolerance to soil acidity was studied in two species of Ericaceae that grow in mine-contaminated soils (S Portugal, SW Spain) to find out if there are interspecific variations in H+ tolerance which might be related to their particular location.MethodsTolerance to H+ toxicity was tested in nutrient solutions using seeds collected in SW Spain. Plant growth and nutrient contents in leaves, stems and roots were determined. Viability tests and proton exchange were studied in roots exposed, short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the hydroponic culture, similar results were also observed in soybean roots, except for Fe concentration, which was slightly increased but not significant (Figure S2). Other study of Erica also showed that acidity stress significantly affected the Mg and Mn concentrations in leaves, S, B and Fe concentrations in stems, and Ca, P, Fe, Cu and Zn concentrations in roots [25]. Thus, these results strongly suggested that the capability of mineral nutrients acquisition and translocation in plants could be influenced by proton toxicity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the hydroponic culture, similar results were also observed in soybean roots, except for Fe concentration, which was slightly increased but not significant (Figure S2). Other study of Erica also showed that acidity stress significantly affected the Mg and Mn concentrations in leaves, S, B and Fe concentrations in stems, and Ca, P, Fe, Cu and Zn concentrations in roots [25]. Thus, these results strongly suggested that the capability of mineral nutrients acquisition and translocation in plants could be influenced by proton toxicity.…”
Section: Discussionmentioning
confidence: 74%
“…Accompanied with root growth inhibition, low-pH stress can disturb plant mineral nutrient acquisition mainly through destruction of proton gradients across plasma membranes [14,15,16,21,22,23,24,25]. One typical example is the nitrate (NO 3 − ) up-take in plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…Very low apoplastic pH is relevant in some naturally acidic waters (e.g. pH as low as 2.3; Rossini Oliva et al, 2009Oliva et al, , 2018. Therefore, the ability of RG-II to remain stably boron-bridged, or to undergo de-novo boron bridging, in acidic environments is biologically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Boron (B) is a trace element that is necessary for better plant growth and development. Boron participates in the stability of plant cell walls, cell membranes, carbohydrate transport, protein, and nucleic acid metabolism (O'Neill et al 2004;Rossini et al 2018;Fang et al 2019). B is found in the soil as boric acid, which is highly soluble (Yan et al 2019b).…”
Section: Introductionmentioning
confidence: 99%